Neonatal grief and the role of psychology in this context (Research, Society and Development, 2021)
Currently, death in childhood is uncommon, considering all the modern resources that are available today, namely, prenatal care, neonatal ICU, among others. For this reason, when affected by this fatality, the family feels strangeness and strong impact. The loss of a baby can produce intolerable pain, since it means frustration of desires, fantasies, daydreams and not least, the impotence before the possibility of applying your ability to be a mother / father. In this sense, the need for professionals such as the psychologist is emphasized, in order to help the family to cope with parental mourning and the elaboration of the loss of a child. Thus, this study aimed to talk about the importance of psychological intervention in grieving situations: perinatal and neonatal. From a qualitative research, from a bibliographic review, it was possible to identify that this type of mourning goes against what is culturally expected in our society about the life cycle. That said, in view of what these losses can cause in families and even in health teams, the presence of the psychologist in this context is necessary. Consubstantially, the importance of future studies that may invest in new reflections on perinatal mourning is emphasized, since the considerations brought by them may have implications for the psychologist's practice in the hospital environment.